Is There a Pragmatist Approach to Literature? - Gunn, Giles (Complutense Journal of English Studies, 2014)
This article explores the relation between literature as a form of artistic understanding and pragmatism as a form of philosophical inquiry. It does so, first, by exploring the place that each similarly accords the imagination as an instrument both of knowing and of making. The American philosopher John Dewey expressed the nature of this linkage when he argued that the purpose of art – and, he could have added, of pragmatic reflection as well – is to contrast actual conditions and their probable consequences with the purely plausible outcomes of experiences that are merely potential. Second, it shows how the cognitive needs served in this way by both literature and pragmatic philosophy converge around a double truth. Just as we need forms to express and experience what would otherwise go unsaid and thus unfelt and unknown, so we also need forms that also help us retrieve what we have already experienced or understood but have then either forgotten or suppressed. Literary and philosophical forms serve both these functions by at once taking us out of ourselves to experience what is strange and foreign on the peripheries of our understanding and also return us to the center of our experience where we so often recover a sense of the strangeness and foreignness that is already within it. Third, this article discusses how these strategies have found expression in a tradition of American writing that begins with Emerson and continues down the present and is marked by a special kind of linguistic skepticism.